New species and a new record of the mite family Scutacaridae (Acari: Heterostigmata) from alpine New Zealand - Khaustov, Alexander A.; Minor, Maria A. (Zootaxa, 2018)
Seven new species of the mite family Scutacaridae (Acari: Pygmephoroidea) are described from the alpine zone (1600–1900 m a.s.l.) of the Central Otago region of the South Island of New Zealand: Diversipes laticaudatus sp. nov., Scutacarus isotrichus sp. nov., S. incisus sp. nov., S. spinisetus sp. nov., S. cornutus sp. nov., S. novaezealandicus sp. nov., and S. crassus sp. nov. In addition, Imparipes woodi Mahunka, 1974 is recorded from the New Zealand for the first time and redescribed.